Sewing Terms in Proverbs: Stitching Linguistic and Cultural Wisdom - Hakimova Ziyoda Tohirjon qizi (Zien Journals, 2023)
This article defines using sewing terms in proverbs. It includes some proverbs containing sewing terms and analyze their functions. The linguocultural aspect of sewing terms in proverbs provides a glimpse into the interplay between language, culture, and the craft of sewing. These proverbs contain valuable lessons and insights, drawing upon sewing terminology to convey wisdom
Keywords: sewing terms; provrebs; linguocultural aspect